PERAN DAN KEDUDUKAN HUKUM DALAM MENGATUR HUBUNGAN SOSIAL - Tanjung, Mhd. Ridwan (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2025)
Law has a very important role and position in regulating social relations in society. Law acts as a regulatory tool, which aims to create order, justice, and social welfare. This article examines the positive and negative impacts of law enforcement, supported by theoretical perspectives such as social control and social engineering. The role of law in regulating social norms such as, managing conflict, and ensuring social justice is emphasized in society, along with the challenges of rigidity and abuse of authority by law enforcers. A responsive and fair legal system is needed to realize a just and prosperous society.